Capacity of Nigerian national institutions to conduct biotechnology research to improve livestock productivity - Omitogun, O.G.; Osoniyi, R.O. (TSAP and ILRI, 2006)
Biotechnology development has been the subject of interest in Nigeria over the past decade. As part of the study by the International Livestock Research Institute (ILRI) sponsored by the US Agency for International Development (USAID) to investigate the development and/or prospects of biotechnology tools as applied to animal science research in Nigeria, a survey aimed at assessing biotechnology capacity of Nigeria for animal research was conducted between June and July 2004. The survey used a structured questionnaire, interviews and personal visits to some universities, polytechnics and national research institutions situated in strategic locations in Nigeria. Though a general deterioration of facilities in most universities was noted, there are quite a number of institutions identified to be capable of applying some biotechnology tools to improve animal production in Nigeria. There are well-trained Nigerian researchers in the country who when supplied with tools in biotechnology and financial support to carry out well-focused or coordinated research can help propel the country towards self-sufficiency in animal production. The role of ILRI and development investors like USAID in making significant intervention in the attainment of this goal is highlighted.